2018
DOI: 10.1111/joa.12795
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent changes in bone healing capacity of scaphoid fractures and non‐unions

Abstract: The scaphoid is the most frequently fractured carpal bone and prone to non‐union due to mechanical and biological factors. Whereas the importance of stability is well documented, the evaluation of biological activity is mostly limited to the assessment of vascularity. The purpose of this study was to select histological and immunocytochemical parameters that could be used to assess healing potential after scaphoid fractures and to correlate these findings with time intervals after fracture for the three parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
0
15
0
6
Order By: Relevance
“…24,25 SNUs are not healed fractures, but living bone alongside the nonunion site preserves its healing capacity. 26 They have a lower healing potential compared with simple fractures. 27,28 Schmidle et al found that the healing capacity depends on the time passed out from trauma concerning the distal pole and gap region; conversely, there is limited healing capacity of the proximal pole already at early stages, with few alterations over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 SNUs are not healed fractures, but living bone alongside the nonunion site preserves its healing capacity. 26 They have a lower healing potential compared with simple fractures. 27,28 Schmidle et al found that the healing capacity depends on the time passed out from trauma concerning the distal pole and gap region; conversely, there is limited healing capacity of the proximal pole already at early stages, with few alterations over time.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Schmidle et al found that the healing capacity depends on the time passed out from trauma concerning the distal pole and gap region; conversely, there is limited healing capacity of the proximal pole already at early stages, with few alterations over time. 26 Trusting in potential healing, some authors have reported positive results of fixed SNUs without bone grafting. [29][30][31] However, these studies are heterogeneous considering the population, techniques, and assessment of results, even if they reported promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Hinsichtlich der gegenwärtig aufflammenden Diskussion über die Notwendigkeit vaskularisierter Knochentransplantate [1,2,32,33] ist eine objektive Klärung einerseits dringend erforderlich, andererseits methodisch nach unserem Dafürhalten wegen mangelnder Vergleichbarkeit unterschiedlicher Patientengruppen nahezu unmöglich. Dies wird auch nicht besser durch immer umfassendere Metaanalysen, da dieses Aufblähen von Fallzahlen die eigentliche Datengrundlage in der Realität verwässert und eine Pseudogenauigkeit generiert.…”
Section: Degenerative Veränderungenunclassified
“…In einer histologischen Studie konnten wir zeigen, dass im proximalen Fragment unabhängig von der Zeitdauer des Bestehens der verzögerten Knochenheilung resp. Pseudarthrose das Knochenheilungspotential reduziert ist [29]. Mit zunehmendem Fraktur-/Pseudarthrosenalter nahm die biologische Aktivität allerdings auch im distalen Fragment ab.…”
Section: Frakturlokalisationunclassified